Number of Relationships Between Abnormal Values in Oral Glucose Tolerance Test and Adverse Pregnancy Outcome - Burak Bayraktar; Meriç Balıkoğlu; Miyase Gizem Bayraktar; Ahkam Göksel Kanmaz (Indian Journal of Medical Specialities)
Objective: The aim of this study is to investigate the effect of detecting one or more positive values in 75 g oral glucose tolerance test (OGTT) performed between 24 and 28 gestational weeks on neonatal biometry (macrosomia, newborn weight, head circumference, and body length of newborn), obstetric results, and treatment requirement. Materials and Methods: Between January 2019 and December 2020 at the University of Health Sciences Tepecik Training and Research Hospital, pregnant women who underwent 75 g OGTT between 24 and 28 gestational weeks and had singleton pregnancy were included in the study. Multiple pregnancies, pregnancies with gestational age <37 and ≥42 weeks, pregestational diabetes mellitus, pregnancies with intrauterine growth retardation, those with chromosomal and/or congenital anomalies, those with thyroid disease, pregnant women whose information could not be reached, and/or whose information was deficient were excluded from the study. These pregnant women were classified into Group 1 with a positive single value, Group 2 with two positive values, and Group 3 with all positive values according to 75 g OGTT values. Results: Two hundred and eighty-three singleton-term and gestational diabetic pregnant women who met the inclusion criteria were included in the analysis. The age of pregnant women and their body mass index (pre-pregnancy and at during test) increased from Group 1 to Group 3, and the differences between all groups were significant (P < 0.001, P < 0.001 and P < 0.001, respectively). The number of pregnant women treated with insulin increased significantly from group 1 to group 3 (P<0.001). Birth weight and body length of new-borns were significantly higher in Group 3 as compared to Group 1 and Group 2 (P = 0.033 and P = 0.017, respectively). Macrosomia prevalence was the highest in Group 3 with 21.7% (P < 0.001). Conclusion: The number of positive values detected between 24 and 28 weeks of gestation in 75 g OGTT was associated with the birth weight, body length, and macrosomia of the newborn and also could be used as an early biomarker to mother's insulin requirement.